Diffuse B Cell Non-Hodgkin’s Lymphoma Presenting Atypically as Periprosthetic Joint Infection in a Total Hip Replacement - Aysha Rajeev; Angela Ralte; Nameer Choudhry; Faizan Jabbar; Paul Banaszkiewicz (Case Reports in Orthopedics)
The occurrence of extranodal primary B cell non-Hodgkin’s lymphoma is rare. Total hip replacement is one of the most common orthopaedic procedures performed. There has been an increased incidence of primary lymphomas involving periprosthetic sites. Chronic inflammation due to metal debris arising from the prosthetic implants has been evidenced as one of the causes for the development of soft tissue lymphomas albeit rarely. We describe a case report of a 77-year-old patient who had underwent a cemented total hip replacement in the past who further developed large B cell primary non-Hodgkin’s lymphoma. She presented initially with signs and symptoms highly suggestive of underlying periprosthetic infection. The radiological imaging was also indicative of periprosthetic infection. The diagnosis was eventually confirmed after an open biopsy. This case underlines the importance of considering and including soft tissue malignancy in the differential diagnosis of suspected chronic periprosthetic infection.